2013
DOI: 10.1152/jn.00431.2013
|View full text |Cite
|
Sign up to set email alerts
|

Action of octopamine and tyramine on muscles ofDrosophila melanogasterlarvae

Abstract: Octopamine (OA) and tyramine (TA) play important roles in homeostatic mechanisms, behavior, and modulation of neuromuscular junctions in arthropods. However, direct actions of these amines on muscle force production that are distinct from effects at the neuromuscular synapse have not been well studied. We utilize the technical benefits of the Drosophila larval preparation to distinguish the effects of OA and TA on the neuromuscular synapse from their effects on contractility of muscle cells. In contrast to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 85 publications
3
49
0
Order By: Relevance
“…∼5-25 on muscles 13 and 4). This difference in innervation is easily understood given that glutamate directly elicits electrical excitation, while octopamine regulates basal and evoked larval muscle contractility (Ormerod et al, 2013) and development of glutamatergic synapses even on muscles lacking type II innervation (Koon et al, 2011). Thus, identified Drosophila octopamine neurons offer the opportunity to elucidate how organelles are distributed in an extensive field of monoaminergic innervation from a single axon associated with neurohormone action reminiscent of monoaminergic volume transmission in the mammalian brain.…”
Section: Introductionmentioning
confidence: 99%
“…∼5-25 on muscles 13 and 4). This difference in innervation is easily understood given that glutamate directly elicits electrical excitation, while octopamine regulates basal and evoked larval muscle contractility (Ormerod et al, 2013) and development of glutamatergic synapses even on muscles lacking type II innervation (Koon et al, 2011). Thus, identified Drosophila octopamine neurons offer the opportunity to elucidate how organelles are distributed in an extensive field of monoaminergic innervation from a single axon associated with neurohormone action reminiscent of monoaminergic volume transmission in the mammalian brain.…”
Section: Introductionmentioning
confidence: 99%
“…There were no qualitative differences between the two salines with regard to the ability of the peptide to enhance contractions. We have also previously demonstrated that these two salines do not alter octopamine-induced enhancements of EJPs (Ormerod et al 2013). Larvae were dissected as described above for EJP recordings.…”
Section: Force Recordingsmentioning
confidence: 95%
“…7), force was detected using a custom force transducer composed of four silicon wafer strain gauges (Micron Instruments, Simi Valley, CA) in full Wheatstone bridge configuration and mounted about the narrowest part of a polycarbonate beam (Ormerod et al 2013;Paterson et al 2010). The transducer operates linearly between 1 N and 2 N and exhibited no temperature sensitivity between 10 and 30°C.…”
Section: Force Recordingsmentioning
confidence: 99%
See 2 more Smart Citations